Implementation of The Occupational Safety and Health Program In The Mining Sector (Case Study In The Mining Area of Morowali Regency, Central Sulawesi) - Akhmad Fahrul Akhmad; Juanda Nawawi; Muhammad Rusdi (Journal of Government Science Studies, 2026)
One area experiencing rapid development in this sector is Morowali Regency, Central Sulawesi, especially following the establishment of the PT Indonesia Morowali Industrial Park (IMIP) industrial area as a nickel processing center. This industrial growth has boosted the regional economy, but has also given rise to various problems, particularly related to occupational safety and health (OHS). Mining activities involving the use of heavy equipment, hazardous materials, and complex working conditions make this sector a high risk of occupational accidents. Several reports indicate that a number of occupational accident incidents still occur in the IMIP industrial area, indicating that the implementation of OHS policies has not been fully optimal. This study aims to analyze the process of OHS policy implementation in the mining sector in Morowali Regency and identify factors that influence its effectiveness. The study used a qualitative approach with a descriptive type, conducted in the PT Indonesia Morowali Industrial Park (IMIP) area. Data collection techniques were carried out through observation and interviews with purposively selected informants. Data analysis used an interactive analysis model that includes data reduction, data presentation, and conclusion drawing, supported by the Interpretative Phenomenological Analysis (IPA) approach. The results of the study indicate that normatively the OHS policy has complied with national regulations, but its implementation in the field still faces various obstacles such as low worker understanding of safety procedures, differences in compliance levels between main companies and subcontractors, and weak utilization of incident reporting systems. The effectiveness of the implementation of the OHS policy is influenced by communication factors, the quality of human resources, the organizational bureaucratic structure, and the skills of workers in applying OHS principles.).